2012
DOI: 10.7314/apjcp.2012.13.8.4063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Breast Cancer BI-RADS 4 Lesions During 2003-2008 in the National Cancer Institute Thailand

Abstract: To determine the clinical outcome of breast cancer BI-RADS 4 lesions and seek a more effective management guideline, we conducted a retrospective study of all BI-RADS4 patients diagnosed between 2003-2008 with follow up time not less than 2 years. A total of 392 cases of BI-RADS 4 were identified and 320 could be sub-categorised as 4a, 4b and 4c. Overall malignant positive results were 7.65, 38.7 and 58.percent, respectively. In all cases assigned to the close follow up group, no malignancy was detectable (P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…However, this was not completely in line with certain previous researches in which BI‐RADS score of 4 was mostly used as the cutoff value for benign and malignant lesions . Chaiwerawattana et al conducted a retrospective study of BI‐RADS 4 patients diagnosed in the National Cancer Institute Thailand during 2003‐2008, which showed that the malignant positive rates of 4A, 4B, and 4C patients were 7.7%, 38.7%, and 58.0%, respectively . In another study published by Elezaby et al, with 41 841 patients classified as BI‐RADS 4, the positive predictive values of 4A, 4B, and 4C patients were 7.6%, 22.0%, and 69.3%, respectively .…”
Section: Discussionmentioning
confidence: 89%
“…However, this was not completely in line with certain previous researches in which BI‐RADS score of 4 was mostly used as the cutoff value for benign and malignant lesions . Chaiwerawattana et al conducted a retrospective study of BI‐RADS 4 patients diagnosed in the National Cancer Institute Thailand during 2003‐2008, which showed that the malignant positive rates of 4A, 4B, and 4C patients were 7.7%, 38.7%, and 58.0%, respectively . In another study published by Elezaby et al, with 41 841 patients classified as BI‐RADS 4, the positive predictive values of 4A, 4B, and 4C patients were 7.6%, 22.0%, and 69.3%, respectively .…”
Section: Discussionmentioning
confidence: 89%
“…In 2012, Chaiwerawattana et al compared BI-RADS 4 subgroups and attempted to detect differences between the subgroups in terms of survival rates [11]. They concluded that unnecessary biopsies could be avoided by accurate assessment of the subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…BI‐RADS 4 category and its subgroups (i.e., A, B, and C) do not have well defined criteria and the reported malignancy rates for patients in this category show a very wide variation between 2% and 95%. Several recent studies have searched alternative approaches to reduce the false‐positivity associated with biopsy results in these patients including a short‐interval follow‐up schedule . In a multi‐center study by Bluemke et al.…”
Section: Discussionmentioning
confidence: 99%